Development of E-Modules Based on Puger Marine Local Potential to Improve students’ Creative Thinking Ability in Junior High school Science Learning - Dharmawan, Wahyu; Wahyuni, Sri; Fadilah, Rizka Elan; Juwanda, Kuntoro (Universitas Negeri Semarang, 2025)
Creative thinking ability is the ability of students to generate new ideas and ideas and solve problems by creating innovative solutions. The purpose of this study was to assess the validity, practicality, and effectiveness of e-modules based on the local potential of Puger marine in improving students' creative thinking skills. This research uses the ADDIE development model which includes five main stages, namely analysis, design, development, implementation, and evaluation. The results showed that the percentage of validity of the Puger e-module was 90%, the percentage of practicality of the e-module based on the local marine potential of Puger was 86%, the percentage of effectiveness of the e-module based on the local marine potential of Puger was 91% and the n-gain value was 0.68 so that the e-module based on the local marine potential of Puger was concluded to be valid, practical, and effective to improve students' creative thinking skills in science learning in junior high school. Puger as a marine potential in Jember can be utilized as a learning resource, making it easier for students to understand learning because it is close to everyday life.